1967
DOI: 10.1002/bit.260090210
|View full text |Cite
|
Sign up to set email alerts
|

Production of Semliki Forest Virus from hamster kidney cells in deep culture vessels

Abstract: The growth of Semliki Forest Virus in st,irred culture vessels at volumes of 4 and 30 1. is described. Virus can be produced on a large scale in deep culture using industrial type vessels. Control of pII within close limits is important for maximum production of itifective virus. With the parent strain of SFV, virus yields were found to be influenced by an interference phenomenon which was apparently not due to interferon. Growth of a cloned strain of SFV obtained by serial selection of large plaques was not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
1975
1975

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…could be used to seed a 400 1. culture vessel without a reduction in the titre of peak virus. It is of interest that Telling, Radlett & Mowat (1967), using the same cell system, found that Semliki Forest virus yield increased as the input virus decreased.…”
Section: Discussionmentioning
confidence: 99%
“…could be used to seed a 400 1. culture vessel without a reduction in the titre of peak virus. It is of interest that Telling, Radlett & Mowat (1967), using the same cell system, found that Semliki Forest virus yield increased as the input virus decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The cap has been drilled and tapped to accept a bulkhead quickconnect [S] and two * in. pipe plugs [9]. These plugs have beon drilled through (+ in.)…”
Section: Spinner Flaskmentioning
confidence: 99%